Transmission expansion planning via a constructive heuristic algorithm in restructured electricity industry - Khorasani, H. [UNESP]; Pourakbari-Kasmaei, M. [UNESP]; Romero, R. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2013)
The transmission expansion planning problem in modern power systems is a large-scale, mixed-integer, nonlinear and non-convex problem. this paper presents a new mathematical model and a constructive heuristic algorithm (CHA) for solving transmission expansion planning problem under new environment of electricity restructuring. CHA finds an acceptable solution in an iterative process, where in each step a circuit is chosen using a sensitivity index and added to the system. The proposed model consider multiple generation scenarios therefore the methodology finds high quality solution in which it allows the power system operate adequacy in an environment with multiple generators scenarios. Case studies and simulation results using test systems show possibility of using Constructive heuristic algorithm in an open access system. © 2013 IEEE.
Keywords: Constructive heuristic algorithm; hybrid model; Multiple generating scenarios; Open access; Transmission expansion planning